The Effect of Third Party Funds and Murabahah Margin Income through Corporate Social Responsibility (CSR) as Intervening Variables on Bank North Sumatra Syariah's Profit in 2019-2022 - Raisa Muthia Syahrani Hasibuan; Tuti Anggraini; Khairina Tambunan (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2023)
One of the indicators of the viability of a bank is its profit. Profitability is an important indicator for the long-term survival of the operation of Islamic institutions. The formulation of this research problem is whether DPK and murabahah margin have a partial and simultaneous effect on CSR. Is there a simultaneous and partial influence of deposits, murabahah margins, and CSR on Bank Sumut Syariah's profits? Can CSR mitigate the impact of deposits and murabahah margins on Bank Sumut Syariah's profits? The research method used is the quantitative research method with a purposive sampling technique. Secondary data in the form of quarterly financial statements of Bank Sumut Syariah is used for the 2019-2022 period. Classical assumption tests, multiple linear regression analysis, t-tests, F tests, coefficients of determination, and path analysis are used for data analysis. The results of this study show that: (1) Deposit margin and murabahah affect CSR, as shown by the findings of this study (2) Deposit and murabahah margin affect Bank Sumut Syariah's profit (3) CSR does not have an impact on Bank Sumut Syariah's income. The effect of deposits and murabahah margins on Bank Sumut Syariah's profit cannot be mediated by CSR as an intervening variable. Islamic banking is expected to increase profit generation so as to maintain bank operational stability by increasing fund collection and optimizing incoming revenue, based on research results.